The cornerstone of modern nursing management - B. Robertson (AOSIS, 1984)
In most professions research is an essential part of the activities of the profession. It not only enables the profession to earn its place in history as a bona-fide profession but it enables it to remain dynamic by evaluating past achievement, improving present practice and collecting data on which to base future decisions.